2004
DOI: 10.1148/radiol.2323030628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monitor Luminance and Ambient Light on Observer Performance in Soft-Copy Reading of Digital Chest Radiographs

Abstract: When adequate window width and level are applied to soft-copy images, the primary diagnosis with chest radiographs on the monitor is unlikely to be affected under low ambient light and a monitor luminance of 25 foot-lamberts or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 13 publications
2
37
1
4
Order By: Relevance
“…Liquid crystal displays (LCDs) are the current electronic display technology for viewing medical digital images. Calibration of the luminance response of each LCD is required to ensure that observer perception of an image is consistent on all displays as the inherent luminance properties of different LCDs can vary considerably (Goo et al, 2004;Fetterly et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Liquid crystal displays (LCDs) are the current electronic display technology for viewing medical digital images. Calibration of the luminance response of each LCD is required to ensure that observer perception of an image is consistent on all displays as the inherent luminance properties of different LCDs can vary considerably (Goo et al, 2004;Fetterly et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Conventionally, it has been thought that ambient lighting should be minimized in reading rooms to maintain perceived image contrast [1,2]. The validity of this convention is supported by studies utilizing film and cathode ray tube (CRT) displays which demonstrated a generally negative effect of increased ambient lighting on chest radiologist performance [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors contribute to image quality in softcopy radiographic and mammographic display [39][40][41][42]. Although the FDA recommends that monitors used for interpretation be specifically cleared for FFDM use by the FDA, the use of others is also legal under MQSA [36].…”
Section: B Softcopy Display Devicesmentioning
confidence: 99%